Effect of Fc Receptor Genetic Diversity on HIV-1 Disease Pathogenesis - Geraghty, Daniel E.; Thorball, Christian W.; Fellay, Jacques; Thomas, Rasmi (Frontiers in Immunology, 2019)
Fc receptor (FcR) genes are highly polymorphic and have been implicated in multiple inflammatory and autoimmune processes. Variation in these genes might also be involved in etiology of infectious diseases. The protective role of Fc-mediated antibody-function in HIV-1 immunity has led to the investigation of specific polymorphisms in FcR genes on acquisition, disease progression and vaccine efficacy in natural history cohorts. The purpose of this review is not only to explore these known HIV-1 host genetic associations, but also to re-evaluate them in the context of genome-wide data. In the current era of effective anti-retroviral therapy, the potential impact of such variation on post-treatment cohorts cannot go unheeded and is discussed here in the light of current findings. Specific polymorphisms associating with HIV-1 have previously been genotyped by assays that captured only the single-nucleotide polymorphism (SNP) of interest without relative information of neighboring variants. With recent technological advances, these highly variable genes can now be characterized using next-generation sequencing, allowing precise annotation of the whole chromosomal region. We herein also discuss updates in the annotation of common FcR variants that have been previously associated with HIV-1 pathogenesis.